Nonsubscription side of periodicals : changes in library operations and costs between print and electronic formats - Schonfeld, Roger C.; Council on Library and Information Resources (CLIR online, 2004)
"Many academic and research libraries are in the midst of what may ultimately be a major transition for various parts of their collections-- a shift from print to electronic format. Libraries that had long subscribed only to print versions of journals are, in increasing numbers, licensing electronic versions to replace the print. What effects will this transition have on library operations and on nonsubscription expenditures? To answer this question, the authors collected new data on staff activities and costs from 11 U.S. academic libraries. They then performed a life-cycle analysis to study the longer-term cost implications of the transition."--Abstract from CLIR web site.
Keywords: Academic libraries : Collection development; Electronic journals; Periodicals; verkkolehdet; yliopistokirjastot; kokoelmatyö